Relatedness of Indian flax genotypes (Linum usitatissimum L.): an inter-simple sequence repeat (ISSR) primer assay - Rajwade, Ashwini V.; Arora, Ritu S.; Kadoo, Narendra Y.; Harsulkar, Abhay M.; Ghorpade, Prakash B.; Gupta, Vidya S. (Molecular Biotechnology, 2010)
The objective of this study was to analyze the genetic relationships, using PCR-based ISSR markers, among 70 Indian flax (Linum usitatissimum L.) genotypes actively utilized in flax breeding programs. Twelve ISSR primers were used for the analysis yielding 136 loci, of which 87 were polymorphic. The average number of amplified loci and the average number of polymorphic loci per primer were 11.3 and 7.25, respectively, while the percent loci polymorphism ranged from 11.1 to 81.8 with an average of 63.9 across all the genotypes. The range of polymorphism information content scores was 0.03-0.49, with an average of 0.18. A dendrogram was generated based on the similarity matrix by the Unweighted Pair Group Method with Arithmetic Mean (UPGMA), wherein the flax genotypes were grouped in five clusters. The Jaccard's similarity coefficient among the genotypes ranged from 0.60 to 0.97. When the omega-3 alpha linolenic acid (ALA) contents of the individual genotypes were correlated with the clusters in the dendrogram, the high ALA containing genotypes were grouped in two clusters. This study identified SLS 50, Ayogi, and Sheetal to be the most diverse genotypes and suggested their use in breeding programs and for developing mapping populations.
Keywords: ALA; Alpha linolenic acid; Diversity assessment; Linseed; Oil content; Omega-3 fatty acid

Role of ions and their transporters in combating salt stress in Pandanus odorifer (Forssk.) Kuntze - Rashmi, Deo; Ansari, Waquar A.; Kadoo, Narendra Y.; Barvkar, Vitthal T.; Deshmukh, Rupesh; Nadaf, Altafhusain B. (Acta Physiologiae Plantarum, 2023)
Soil salinity is a major environmental constraint causing huge losses in crop production. Pandanus odorifer (Forssk.) Kuntze is an aromatic monocot plant species belonging to the family Pandanaceae, which grows naturally on the saline soils along the coasts of Asia, Southeast Asia, and Polynesia. The plants are dioecious and highly fertile, and the consistent saline sprays, strong winds, and severe soil salinity hardly affect their growth and fertility. Hence, understanding the mechanism of high salinity tolerance in P. odorifer could provide major advances in overcoming salinity stress in crop plants. In the present study, we analyzed control (0 M NaCl) and treated (1 M NaCl treatment for 3 weeks) plants of P. odorifer to understand the role of ion distribution, ion transport, and related mechanisms under salt stress. Using a combination of ionomics and transcriptomics approaches, we identified the molecular mechanisms contributing to the high salinity stress in P. odorifer. Under NaCl stress, there was a significant increase in Na, Cl, and other ions in leaves, while the concentrations of Si, Fe, Ni, and Ti decreased. Similarly, in roots, the levels of Na, Mg, Cd, and Cr were significantly high, while the levels of other ions decreased. Most of the genes related to ion transport and homeostasis, such as NHX1, CLC-C, SOS1, HAK, and ABC transporters, were upregulated in 1 M NaCl stress conditions. This study revealed that vacuolar sequestration of Na+ and the distribution of ions in the roots and shoots play significant roles in the salt-stress tolerance mechanism of P. odorifer.
Keywords: Ion transport; Ionomics; Pandanus; Salinity tolerance; Transcriptomics; Vacuolar sequestration